Incidence of tics in the animation of reading in students of 4th EB - Cantos Over, Leyla Johanna; Morocho Choca, Miryan Katherine (Revista Minerva, 2022)
The human being and everything related to his intellectual, physical, moral, personal and attitudinal development has evolved over time. In the same sense, educational institutions have not forgotten this progress as they seek to strengthen their PEI every day to provide a better education to their students. That is why technological tools have been applied in this project, including Web wix, whose main objective is to apply reading strategies to texts that articulate important knowledge, using ICT as a didactic tool for 4th grade students of the Educational Unit Daule, awakening your curious mind and the ability to identify, interpret and use reading skills. Likewise, the type of bibliographical research and quantitative methods at the descriptive level were used, with surveys of teachers. Which evidenced why the use of the Wix network to develop the results of teaching activities, especially in reading skills, guides students to become members of a virtual world, and competent.
Keywords: Strategies; Reading; Teachers; Animation